Suitability of the In Vitro Cytokinesis-Block Micronucleus Test for Genotoxicity Assessment of TiO2 Nanoparticles on SH-SY5Y Cells - Fernández-Bertólez, Natalia (2021)
Standard toxicity tests might not be fully adequate for evaluating nanomaterials since their unique features are also responsible for unexpected interactions. The in vitro cytokinesis-block micronucleus (CBMN) test is recommended for genotoxicity testing, but cytochalasin-B (Cyt-B) may interfere with nanoparticles (NP), leading to inaccurate results. Our objective was to determine whether Cyt-B could interfere with MN induction by TiO2 NP in human SH-SY5Y cells, as assessed by CBMN test. Cells were treated for 6 or 24 h, according to three treatment options: co-treatment with Cyt-B, post-treatment, and delayed co-treatment. Influence of Cyt-B on TiO2 NP cellular uptake and MN induction as evaluated by flow cytometry (FCMN) were also assessed. TiO2 NP were significantly internalized by cells, both in the absence and presence of Cyt-B, indicating that this chemical does not interfere with NP uptake. Dose-dependent increases in MN rates were observed in CBMN test after co-treatment. However, FCMN assay only showed a positive response when Cyt-B was added simultaneously with TiO2 NP, suggesting that Cyt-B might alter CBMN assay results. No differences were observed in the comparisons between the treatment options assessed, suggesting they are not adequate alternatives to avoid Cyt-B interference in the specific conditions tested.